## Solving the Equation: 0.2x(5x-8) + 3.6 = x(x-0.7)

This article will guide you through the steps of solving the given equation: **0.2x(5x-8) + 3.6 = x(x-0.7)**

### Step 1: Expand the Parentheses

First, we need to distribute the terms outside the parentheses:

**0.2x(5x-8):**This becomes**1x² - 1.6x****x(x-0.7):**This becomes**x² - 0.7x**

Our equation now looks like this: **1x² - 1.6x + 3.6 = x² - 0.7x**

### Step 2: Simplify by Combining Like Terms

We can simplify by moving all the terms to one side of the equation:

- Subtract
**x²**from both sides:**-1.6x + 3.6 = -0.7x** - Add
**1.6x**to both sides:**3.6 = 0.9x**

### Step 3: Isolate the Variable

Now, we need to isolate **x** by dividing both sides by **0.9**:

**3.6 / 0.9 = x**

### Step 4: Calculate the Solution

Performing the division, we find the solution:

**x = 4**

### Conclusion

Therefore, the solution to the equation **0.2x(5x-8) + 3.6 = x(x-0.7)** is **x = 4**. You can verify this by substituting **x = 4** back into the original equation and confirming that both sides are equal.